Membangun Interaksi Edukatif yang Bernilai Normatif Melalui Pengajaran Berbasis Aktifitas - Hawa Liberna (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
To solve the problem of students' interest in mathematics, we need a model of interactive learning and not boring. It is important to establish educational interactions, and one of them to do with the activity-based teaching. Learning is an activity-oriented action research and reflective study is conducted in the classroom, as well as aiming to improve the quality of learning. This process is applied to the "boards nailed" to practice, both by teachers and students collectively. The teacher's role is only to the response associated with the wake geometry as flat and square. This evaluation starts with preparing the implementation plan thematic learning with competency standards in the wake circumference flat, square and rectangular wider, as well as applications and problem solving.